RETRACTED: Environmental policy and the environmental situation in the countries of Central Asia - Gulomov Ilhomjon; Rasulova Risligoy (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001